Dosimetric implications of the exposure to the natural sources of irradation - Beninson, Dan Jacobo; Bouville, A.; O Brien, B. J.; Snichs, J. O. (Academia Brasileira de Ciencias; Brasil, 1977)
Fil: Beninson, Dan Jacobo Comisión Nacional de Energía Atómica; Argentina